2006
DOI: 10.3892/ijo.29.3.541
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor injection of small interfering RNA-targeting human papillomavirus 18 E6 and E7 successfully inhibits the growth of cervical cancer

Abstract: Abstract. Human papillomavirus (HPV) 18 is related not only to squamous cell carcinoma of the cervix, but also to adenocarcinoma and small cell carcinoma of the cervix, in which prognosis is known to be poor. Small interfering RNA (siRNA) that targets HPV18 E6 and E7 was tested in HPV18-positive cell lines to investigate its effect and investigate its mechanism of action. Nude mice were also tested in a combination of siRNA and atelocollagen to determine whether it might be useful as a new moleculetargeting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…Previous studies, including our own, have demonstrated that silencing HPV E6/E7, with siRNA or short hairpin RNA (shRNA), leads to cervical cancer cells undergoing apoptosis or senescence [11][12][13][14] and inhibition of tumor growth in vivo. [14][15][16][17] These results suggest that RNAi therapy could be developed for cervical cancer treatment. However, for this treatment to become a reality a number of issues need to be addressed including achieving stable and durable RNAi.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies, including our own, have demonstrated that silencing HPV E6/E7, with siRNA or short hairpin RNA (shRNA), leads to cervical cancer cells undergoing apoptosis or senescence [11][12][13][14] and inhibition of tumor growth in vivo. [14][15][16][17] These results suggest that RNAi therapy could be developed for cervical cancer treatment. However, for this treatment to become a reality a number of issues need to be addressed including achieving stable and durable RNAi.…”
Section: Introductionmentioning
confidence: 93%
“…Although these particles have not been modified to target tumors, passive targeting due to the enhanced permeability and retention effect, causes the selective accumulation within the cancerous tissues as shown in several studies with tumor xenografts. 23,[37][38][39] Initial studies indicated that atelocollagen particles could be administered safely without induction of cytokines or observed toxicity to the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Atelocollagen, which is prepared from bovine dermis, 17,18 contributes to increases in cellular uptake, nuclease resistance and the prolonged release of siRNA, 14,[19][20][21] as well as plasmid DNA, 17 and antisense oligonucleotide compounds, 10,11,13,22 administered to tumors. An siRNAatelocollagen complex also can be delivered via an intravenous injection route as nanoparticles, enabling systemic delivery of siRNAs.…”
mentioning
confidence: 99%